The Caricom Single Market and development in a small town in St Lucia - Henry, Clarence (2008)
Examines the potential of geographical areas such as towns and cities to benefit from the provisions of the CSME. Expects that the higher levels of public and private investment which such an arrangement may bring, if channeled through these towns, promote economic growth and development which could spillover to the national level.